Evaluation of physicochemical properties of hydrocol-loid-based functional food fortified with Caulerpa lentillifera: a d-optimal design mixture approach - Ahmad Nasir, Nor Atikah Husna; Yuswan, Mohd Hafis; Abd Karim Shah, Nor Nadiah; Abd Rashed, Aswir; Kadota, Kazunori; Yusof, Yus Aniza (Multidisciplinary Digital Publishing Institute, 2023)
This study introduced a D-optimal design mixture to assess the physicochemical properties of a hydrocolloid-based functional food fortified with C. lentillifera. The combination incorporated vital jelly constituents, including extract (10–15%), sweeteners (20–29%), gelling agents (k-carrageenan and locust bean gum (LBG)), and preservatives (0–0.05%). The dependent variables were pH, Total Soluble Solid (TSS) value, and moisture content (MS). By employing the D-optimal design approach, a quadratic polynomial model was developed, demonstrating strong correlations with the experimental data with coefficient determinations (R2) of 0.9941, 0.9907, and 0.9989 for pH, TSS, and MS, respectively. Based on the D-optimal design, the study identified the optimum combination of significant factors with a desirability of 0.917, comprising 14.35% extract, 23.00% sucrose, 21.70% fructose, 26.00% k-carrageenan, 13.00% LBG, 1.95% CaCl2, and 0% methylparaben. The percentage of residual standard error (RSE) was less than 5%, indicating the reliability of the developed model. Furthermore, color analysis revealed significant differences among the jellies (p < 0.05). HPLC analysis demonstrated that the total sugar content in the fortified jellies was 28% lower compared to commercial jelly. Meanwhile, the bitterness level according to e-tongue showed a reduction of up to 90.5% when compared to the extract. These findings provide a valuable benchmark for the development of functional food products, ensuring their quality, safety, and extended shelf-life.